Regulator of G-protein signaling 14 (RGS14) is a selective H-Ras effector. - Francis S Willard; Melinda D Willard; Adam J Kimple; Meera Soundararajan; Emily A Oestreich; Xiaoyan Li; Nathaniel A Sowa; Randall J Kimple; Declan A Doyle; Channing J Der; Mark J Zylka; William D Snider; et al. (PLoS ONE)
Background Regulator of G-protein signaling (RGS) proteins have been well-described as accelerators of Galpha-mediated GTP hydrolysis ("GTPase-accelerating proteins" or GAPs). However, RGS proteins with complex domain architectures are now known to regulate much more than Galpha GTPase activity. RGS14 contains tandem Ras-binding domains that have been reported to bind to Rap- but not Ras GTPases in vitro, leading to the suggestion that RGS14 is a Rap-specific effector. However, more recent data from mammals and Drosophila imply that, in vivo, RGS14 may instead be an effector of Ras. Methodology/principal findings Full-length and truncated forms of purified RGS14 protein were found to bind indiscriminately in vitro to both Rap- and Ras-family GTPases, consistent with prior literature reports. In stark contrast, however, we found that in a cellular context RGS14 selectively binds to activated H-Ras and not to Rap isoforms. Co-transfection / co-immunoprecipitation experiments demonstrated the ability of full-length RGS14 to assemble a multiprotein complex with components of the ERK MAPK pathway in a manner dependent on activated H-Ras. Small interfering RNA-mediated knockdown of RGS14 inhibited both nerve growth factor- and basic fibrobast growth factor-mediated neuronal differentiation of PC12 cells, a process which is known to be dependent on Ras-ERK signaling. Conclusions/significance In cells, RGS14 facilitates the formation of a selective Ras.GTP-Raf-MEK-ERK multiprotein complex to promote sustained ERK activation and regulate H-Ras-dependent neuritogenesis. This cellular function for RGS14 is similar but distinct from that recently described for its closely-related paralogue, RGS12, which shares the tandem Ras-binding domain architecture with RGS14.